Model of analysis for the study of governance networks at multiple institutional levels - Alva-Rivera, Miguel Eduardo (Estado, Gobierno y Gestión Pública, 2024)
Government action in public affairs has undergone a broad transformation in recent decades, particularly in the way in which it interacts and collaborates with non-state actors to decide, manage and implement public policies,. This new way of governing is conceptualized as governance in government and public administration. Through an analysis centered on neo-institutional theory with particular emphasis on the Bloomington School and its Workshop on Political Theory and Public Policy Analysis, this paper proposes an analytical model to identify governance networks at multiple institutional levels. a comparative study in three sub-national territories in Latin America demonstrates the usefulness of this model that uses Social Network Analysis to describe the decision-making structure in which different actors interact.